LEARNER’S PSEUDO MENTAL MODEL ON PERFORMING ENGLISH SPEAKING TASK ABILITY - Yudi Hari Rayanto (Universitas Negeri Makassar, 2020)
ABSTRACT The purpose of this research is to find out the causes of pseudo mental model occurred on performing English speaking task ability. This research is conducted to the learners of English department in academic year 2018-2019. This research uses questionnaire as the only instrument. The questionnaire was distributed through WA group of learners English department. 38 learners got a questionnaire but only 28 learners who returned the questionnaire to the researcher. The questionnaire consists of 17 items. This research uses descriptive qualitative whereas the researcher analyzes and describes the questionnaire distributed and returned from learners of English department. Base on the data gained, the result shows that although learners have high motivation on learning English speaking subject, that is 96%, pseudo mental model (nervous, afraid, and less confident)on performing English speaking task ability still occurred. Besides that, it also occurs not only because of learners had problems in language component skills , that is 75%, though in fact in specific problems occurred 57% (problems are not similar) but also in mental model 67% though preparation is prepared well 92%, 78% before conducting and 71% during performing, and the frequency of “always “ being nervous, afraid and less confident is 64%. Moreover, 92% learners are trying to reduce of having pseudo mental model (afraid, nervous, lack confident).